Implementation of Vehicle Ad Hoc Networks for TPBFT on Latency and Fault Tolerance in Blockchain Systems - Liqaa Saadi Mezher; Ayam Mohsen Abbass; Muna Hadi Saleh (Universitas Ahmad Dahlan, 2026)
In this paper, examines the combination of Vehicle Ad hoc Networks (VANETs) and a new consensus mechanism called Trust Practical Byzantine Fault Tolerance (TPBFT) that is aimed at improving latency and fault tolerance of decentralized vehicular networks. The VANETs are described by dynamic topology and mobile node and pose special security as well as reliability issues especially in scalable networks. The conventional Byzantine Fault Tolerance (BFT) protocols are ineffective because they incur communication overhead and scaling problems. This paper suggests TPBFT as a powerful consensus mechanism that is suitable to use in vehicular networks and is effective even when malicious or malfunctioning nodes are involved. To model real-life traffic patterns and communication scenarios, the research methodology presupposes extensive simulations based on Simulation of Urban Mobility (SUMO) tool and real-world Open Street Map (OSM) data with the help of the Python program. The performance of TPBFT is strictly tested and compared to the classic Practical Byzantine Fault Tolerance (PBFT) protocol through the analysis of the consensus latency, system throughput, and fault tolerance resilience. The findings indicate TPBFT has a shorter consensus latency (16 to 28 ms) and a greater throughput compared to PBFT and was more effective in time-constrained vehicular usage. The present work makes TPBFT an effective decentralized mechanism that allows achieving low latency, high throughput, and high resistance to Byzantine failures, offering a safe platform to deploy the blockchain technology in smart transportation systems. The optimization of the energy consumption profile of network nodes, as well as the refinement of the consensus process on the application of blockchain-based VANET architecture into practice, will be the subject of future research.